Acoustic Radiation Force Optical Coherence Elastography of Corneal Tissue - Qu, Yueqiao (IEEE J Sel Top Quantum Electron, 2016)
We report on a real-time acoustic radiation force optical coherence elastography (ARF-OCE) system to map the relative elasticity of corneal tissue. A modulated ARF is used as excitation to vibrate the cornea while OCE serves as detection of tissue response. To show feasibility of detecting mechanical contrast using this method, we performed tissue-equivalent agarose phantom studies with inclusions of a different stiffness. We obtained 3-D elastograms of a healthy cornea and a highly cross-linked cornea. Finally we induced a stiffness change on a small portion of a cornea and observed the differences in displacement.